Respuesta :

-4 1/3 divided by -3/4

= (-4 1/3)  / ( -3/4)

= (-13/3) / (-3/4)

= (-13/3) * (-4/3)

= 52/9

= 5 7/9

Answer

5 7/9 (5 and 7/9)

Answer:  [tex]\frac{52}{9}[/tex] = [tex]5\frac{7}{9}[/tex]

Step-by-step explanation:

  [tex]-4\frac{1}{3}[/tex] ÷ [tex]-\frac{3}{4}[/tex]

= [tex]\frac{-13}{3}[/tex] ÷ [tex]-\frac{3}{4}[/tex]

Keep-Change-Flip

= [tex]\frac{-13}{3}[/tex] x [tex]\frac{-4}{3}[/tex]

= [tex]\frac{-13(-4)}{3(3)}[/tex]

= [tex]\frac{52}{9}[/tex]

= [tex]5\frac{7}{9}[/tex]

ACCESS MORE